Labour Pain With Remifentanil Patient-controlled Analgesia Versus Epidural Analgesia: A Randomized Equivalence Trial. Issue 4 (December 2017) - Logtenberg, S.L.M.; Oude Rengerink, K.; Verhoeven, C.J.; Freeman, L.M.; van den Akker, E.S.A.; Godfried, M.B.; van Beek, E.; Borchert, O.W.H.M.; Schuitemaker, N.; van Woerkens, E.C.S.M.; Hostijn, I.; Middeldorp, J.M.; et al.
Abstract : ( BJOG . 2017;124:652–660) Pain intensity scores and patient satisfaction with analgesia for labor and delivery have been compared between the treatment options of intravenous (IV) remifentanil patient-controlled analgesia (RPCA) and epidural analgesia (EA) in previous studies. EA is considered the more invasive technique and is associated with some adverse events such as hypotension and unintentional dural puncture. Remifentanil is short acting and metabolized quickly, but is also associated with oxygen desaturation and respiratory depression. Patient participation in the decision-making process regarding labor analgesia is an important component of a woman's overall satisfaction. Previous studies in medium or high-risk patients have reported similar satisfaction levels for these 2 treatment options, although better pain relief was found with EA. This study investigated whether the same conclusion about patient satisfaction held for low risk women.